TUMBUH DAN BERKEMBANGNYA PESANTREN DI INDONESIA - BAHARUDDIN, ISMAIL (AIN Padangsidimpuan, 2014)
Islamic education institutions grow and evolve since the advent of Islam to Indonesia, and the process of Islamization in Indonesia can not be separated from theÂ institutions.According to the conclusion of the seminar coming of Islam to Indonesia in Medan in 1963, Islam has entered Indonesia since the first century of the Hegira, or about the seventh or eighth century AD. The first area is the Islamic attended coast of Sumatra, and the first Islamic kingdom in Aceh. The results of the seminar in the field in 1963 also strengthened by the results of the Seminar and grow Sign Islam in Aceh, which was held in 1978.When starting from the results of the seminar means that in about the 7th century and 8th AD has grown centers of Islamic education in Indonesia. Places ongoing Islamic education at the early stage centered in the mosque, mosque, meunasah, rangkang, and Boarding School. On the island of Java.Boarding School who is the